2022
DOI: 10.1002/jccs.202200071
|View full text |Cite
|
Sign up to set email alerts
|

HPLC fingerprint profiles of lucidenic acids from Ganoderma lucidum (lingzhi)

Abstract: Ganoderic acids (GAs) and lucidenic acids (LAs) are the two specific triterpene compositions of Ganoderma lucidum. The HPLC fingerprint profile of GAs has been well‐established, but the reports for LAs were rare. In this study, six new lucidenic acids: H2 (1), H3 (2), I2 (3), I3 (4), K (5), L (6) and nine known compounds: lucidenic acids A (7), B (8), C (9), D2 (10), E2 (11), F (12), N (13), P (14), Q (15), were isolated from a strain of G. lucidum fruiting body (YK‐02). A specific fingerprint of the lucidenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…However, specific GAs have been used to identify the fruiting body of G. lucidum, as described in the US Pharmacopeia (USP) [18]. Our previous report also showed that GAs and LAs can be used in species and strain identification for G. lucidum [5]. These triterpenes are strain-specific and show diverse bioactivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, specific GAs have been used to identify the fruiting body of G. lucidum, as described in the US Pharmacopeia (USP) [18]. Our previous report also showed that GAs and LAs can be used in species and strain identification for G. lucidum [5]. These triterpenes are strain-specific and show diverse bioactivity.…”
Section: Discussionmentioning
confidence: 99%
“…The nineteen triterpenes could be detected in four strains of G. lucidum mycelia, and they all displayed the same HPLC chromatographic pattern, indicating that this HPLC method can be used in the species identification of G. lucidum mycelia. YK-02 and BCRC36090 (Figure 2d,e) are the strains that produce lucidenic acids (LA-type) in their fruit bodies [5]. It was unclear whether GA-type and LA-type fruit bodies produce the same triterpenoid pattern in their mycelia stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations